Assessment of Olfactory Fossa Depth based on Keros Classification using Computerised tomography (Ct) in Age Groups of Both Genders - Mubina Lakhani, Iffat Raza, Rosheena Nabeel Khan, Maria Mohiuddin, Naushin Adnan, Nuzhat Hassan, Mubina Lakhani, Iffat Raza, Rosheena Nabeel Khan, Maria Mohiuddin, Naushin Adnan, Nuzhat Hassan (Journal of Rawalpindi Medical College, 2022)
Objective: Keros classification based assessment of olfactory fossa depth in different age groups of both genders using computerized tomography (CT) Methodology: Cross sectional study done at Ziauddin university, Clifton, Karachi. Sample size was 270 adults including 160 males & 110 females. The assessment of depth of Olfactory fossa was carried out by measuring the height of lateral lamella of cribriform plate on CT images. Result: Olfactory fossa of 270 patients from both sides of both genders were classified according to Keros classification. We found Type II to be the most frequent on both sides in both genders. No significant difference in olfactory fossa depth was found when compared in different age groups. Conclusion: The present study shows that vast majority of the population comes under Keros type II & type III thus emphasizing the need of pre-operative radiological assessment. Association of right & left olfactory fossa depth in different age groups was found to be insignificant.